2002
DOI: 10.1007/s00221-002-1088-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictive responses of periarcuate pursuit neurons to visual target motion

Abstract: The smooth pursuit eye movement system uses retinal information about the image-slip-velocity of the target in order to match the eye-velocity-in-space (i.e., gaze-velocity) to the actual target velocity. To maintain the target image on the fovea during smooth gaze tracking, and to compensate for the long delays involved in processing visual motion information and/or eye velocity commands, the pursuit system must use prediction. We have shown recently that both retinal image-slip-velocity and gaze-velocity sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
104
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(109 citation statements)
references
References 48 publications
5
104
0
Order By: Relevance
“…11B of Fukushima et al 2002a) and were confirmed to be within the caudal FEF in the fundus of the arcuate sulcus. Two other monkeys are still being used for other experiments.…”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…11B of Fukushima et al 2002a) and were confirmed to be within the caudal FEF in the fundus of the arcuate sulcus. Two other monkeys are still being used for other experiments.…”
Section: Methodsmentioning
confidence: 84%
“…The inter-aural midpoint of the animals' heads was positioned close to the axis of horizontal rotation. The target was a laser spot that was back-projected onto the tangent screen 75 cm in front of the animals' eyes (monkey C, Fukushima et al 2000Fukushima et al , 2002a and a 22-inch computer display (Sony) positioned 60 cm in front of the animals' eyes (monkeys SI and SH; e.g., Kasahara et al 2006). Once pursuit-responsive single neurons were encountered, smooth pursuit responses were tested in 4 planes (vertical, horizontal and two oblique planes at 45° angles) to determine the preferred direction.…”
Section: Methodsmentioning
confidence: 99%
“…Traces that contained saccades or slow eye movement were removed since they were indicative of the monkeys' failure to fixate the stationary target, and only those traces with eye position changes of less than 1° during each cycle were analyzed as described previously (Fukushima et al 2000(Fukushima et al , 2002aAkao et al 2005). …”
Section: Methodsmentioning
confidence: 99%
“…Recording locations were histologically confirmed to be within the fundus of the arcuate sulcus by making electrolytic lesions through the recording electrodes as previously described (Tanaka and Fukushima 1998;Fukushima et al 2000Fukushima et al , 2002aJ Fukushima et al 2004).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation